Impact of Technology on Human Life (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Presently technology has become an essential part of our life. It fulfills our daily needs. It is used to communicate, to learn, to travel, to enhance business and to live in comfort. It provides improvement in every aspect of life. It makes our life easy. We cannot suppose hassle-free life without technology these days. Every step of our life is dependent on technology. Technology provides us better solutions of most of problems. In the last decades, it has grown rapidly and contributed in businesses. The network of services has become easy, production cost decreased and yield has increased. Technology becomes us more efficient to do complex tasks. It leads to modernization of whole world in different fields such as health care, education, research, medical, engineering and industrialization. This paper will provide positive and negative impacts of technology on human being and how human behavior affects the society as a whole